PROSPECT OF ENLARGEMENT OF BUSINESS DEVELOPMENT GOLDFISH IN A POOL OF WATER RUSHING IN THE VILLAGE AEK LIBUNG DISTRICT OF SAYUR MATINGGI SOUTH TAPANULI PROVINCE OF NORTH SUMATRA - Imam Faisal Daulay Faisal Daulay; Eni Yulinda; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research about the prospect of enlargement of business development carp in ponds jetted held in July until August 2014 in the Village Aek Libung District of Sayur Matinggi South Tapanuli, North Sumatra. The aims is to know carp rearing operations, feasibility and development prospects business. The method used to this study is a survey respondents with the determination of the census conducted using the entire population of carp farmers as much as 8 people.The results of this study showed an enlargement of carp in ponds heavy feasible to be developed with the largest total investment Rp.10.280.000 produce BCR 1.25 by 24.14% FRR and PPC 4.85. Business prospects enlargement is quite large carp with availability of agribusiness systems and the smooth operation of the work done. This shows the efforts of carp worth continuing enlargement seen from the investment criteria.Keywords: Enlargement Goldfish, Running water system, Feasibility, Investment.